Impulso y arrastre desde el sector agrícola: una posibilidad para minimizar los impactos causados por el covid -19 en Colombia. (2022)
The monograph presents an analysis of the Colombian economy, where it goes from the variations presented in the GDP from 2006 to 2020, in such a way that it allows to demonstrate the impacts caused by COVID-19 in this last year. In this way, the results are contrasted with our main tool: the Colombian input-output matrix for the year 2017 base 2015, from which several mathematical and economic means are derived, such as the technical coefficients, direct and indirect multiplier effects and the total effects. . The same matrix is ​​used to obtain the weighted effects, thanks to this it can be checked whether it is really possible in Colombia to minimize the impacts caused by COVID-19 through agriculture due to the driving and dragging effects of the economy. . Thus, the finding is given that the only branch related to the primary sector that could have enough possibility to generate a push-pull effect is “Live animals and animal products”. Additionally, it is concluded that the branch with the greatest capacity to minimize the impacts caused by COVID-19 and generate an economic growth factor is "Basic Chemicals", understanding that this generates a much higher impulse factor than the rest along with a drag effect. very important, understanding that through this branch you can reach many more, since it is one of the most demanded but at the same time one in which its offer is vital for the rest of the branches, understanding that it is done use of this to generate products with greater added value.